Tertiary lymphoid structures in the primary tumor site of patients with cancer-associated myositis: A case–control study - Kadota, Hiroko; Gono, Takahisa; Kunugi, Shinobu; Ota, Yuko; Takeno, Mitsuhiro; Seike, Masahiro; Shimizu, Akira; Kuwana, Masataka (Frontiers in Medicine, 2023)
Objective To investigate histologic features of immunological components in the primary tumor site of patients with cancer-associated myositis (CAM) by focusing on tumor-infiltrating lymphocytes (TILs) and tertiary lymphoid structures (TLSs), which play major roles in antitumor immunity. Methods Cancer-associated myositis patients were selected from the single-center idiopathic inflammatory myopathy cohort based on the availability of primary tumor specimens obtained before the introduction of immunomodulatory agents. Control cancer subjects without CAM were selected from the cancer tissue repository at a ratio of 1:2 matched for demographics and cancer characteristics of CAM cases. A series of immunohistochemical analyses was conducted using sequential tumor sections. TLS was defined as an ectopic lymphoid-like structure composed of DC-LAMP+ mature dendritic cells, CD23+ follicular dendritic cells (FDCs) and PNAd+ high endothelial venules. TLS distribution was classified into the tumor center, invasive margin, and peritumoral area. Results Six CAM patients and 12 matched non-CAM controls were eligible for the study. There was no apparent difference in the density or distribution of TILs between the groups. TLSs were found in 3 CAM patients (50%) and 4 non-CAM controls (33%). TLSs were exclusively located at the tumor center or invasive margin in CAM cases but were mainly found in the peritumoral area in non-CAM controls. FDCs and class-switched B cells colocalized with follicular helper T cells were abundantly found in the germinal center-like area of TLSs from CAM patients compared with those from non-CAM controls. Conclusion The adaptive immune response within TLSs in the primary tumor site might contribute to the pathogenic process of CAM.